Peran Perbandingan Hukum Pidana Terhadap Kebijakan Formulasi Delik Memperdagangkan Pengaruh (Trading In Influence) Sebagai Tindak Pidana Korupsi - Adhari, Ade; Aprilia, Indah Siti; Widyawati, Anis (UI Scholars Hub, 2023)
Corruption is a criminal act that is intrinsically a disgraceful act because of its destructive power not only to social welfare, but also to the moral values that have been agreed upon and implemented by the Indonesian nation. In all its types and forms, corrupt practices should be qualified as criminal acts through policy formulation of criminal law norms. The act of trading influence in a global perspective is a type of criminal act of corruption, and practically occurs a lot in Indonesia. This can be observed in the cases of sugar import quotas, construction of sports centers and cattle import quotas. Because the current policy formulation has not yet criminalized the act of trading influence, the rules for criminalizing bribery offenses are imposed as a basis for justification for imposing criminal penalties on acts that should constitute the offense of trading influence. This article examines the comparative role of criminal law in the policy formulation of the offense of trading influence as a criminal act of corruption. The results of the research show that through a comparison of criminal law with policy formulation of the offense of trading influence, the study acts as (1) the basis for harmonization of criminal law policies in overcoming criminal acts of corruption in Indonesia at the global level; and (2) finding the elements of the offense of trafficking in influence.